Evaluation of catalytic activity of MeOx/sepiolite in benzyl alcohol oxidation - Nguyen, Tien Thao (H. : ĐHQGHN, 2018)
A series of MeOx/sepiolite (Me ¼Cu, Cr, Mn, Co, Ni) catalysts was prepared through the deposition eprecipitation and characterized by means of XRD, EDS, SEM, BET, and H2-TPR. The structural charac-terization showed a fine distribution of MeOx metal oxides on magnesium silicate nanobars. The sepiolite-loaded-metal oxide catalysts have been screened for the partial oxidation of benzyl alcohol and shown a good conversion and a very high selectivity to benzaldehyde at mild conditions. Under similar experiments, the catalytic activity of the transition metal oxides on sepiolite decreased in the order of Cr>Co>Cu>Mn>Ni. The productivity of benzaldehyde was associated with the behavior of transition metal ions and reaction temperatures.